Listening for lions - Whelan, Gloria (HarperCollins Publ., 2005)
Left an orphan after the influenza epidemic in British East Africa in 1918, thirteen-year-old Rachel is tricked into assuming a deceased neighbor's identity to travel to England, where her only dream is to return to Africa and rebuild her parents' mission hospital.